The Effect of Sleep Pattern on Reproductive Hormones in Females - Abdulqader, Marwa Jasim; Kadhum, Hanaa Salman; Naser, Olaabdul Shaheed (American Journal of Biomedicine and Pharmacy, 2025)
Background: Sleep is the body's rest cycle. Sleep has stimulated by a complex set of mainly active hormones, which respond to signals from the body itself and it’s environment. Methodology: This study was conducted on 50 women from the population with age of (18_25) years old,25 women who suffer from a sleep disorder were considered as a case group and other 25 women with normal and regulated sleep were considered as control group. Samples were collected during the menstrual cycle, by using a gel tube to measure the levels of the following hormones (FSH, LH, Progesterone, E2). Results: The study showed a statistical significant increase in the level of progesterone) p = 0.001) and a decrease in the level of FSH (p=0.02), while the other parameters including study show that there isn’t significant difference between two groups. Conclusion: Sleep disturbance may have a significant impact on a woman's health.